Laundry Majapahit: Pemanfaatan Scripted User Generated Content sebagai Strategi Komunikasi Pemasaran Rinso di TikTok - Geraldo Armayudha; Amiruddin Saleh; Harvia Atika Zahira (Research and Community Service UNIVERSITAS KALBIS, 2026)
This study aims to analyze the use of scripted user generated content as Rinso’s digital marketing communication strategy through the Laundry Majapahit content on TikTok and to examine the storytelling strategies used to convey brand messages and build audience engagement. This study employed a qualitative approach with a case study design and qualitative content analysis. Data were collected through an interview with a key informant from Unilever Indonesia, observation of 19 TikTok posts from the @yatimajapahit account uploaded from October 18 to November 2, 2025, and analysis of audience comments. The findings show that Laundry Majapahit operates as scripted user generated content through a fictional account, the persona of Bu Yati, creator participation, comment responses, and a low-cost manual laundry gimmick. This strategy creates an organic impression, encourages viral marketing, expands electronic word of mouth, and strengthens brand engagement through storytelling and soft selling.